Sexual Size Dimorphism and Age in Odontophrynus cf. barrioi (Anura: Odontophrynidae) from the Monte Desert, Argentina - Quiroga, Lorena Beatriz (2015)
Current knowledge on sexual dimorphism and population structure in the genus Odontophrynus is limited. We studied age structure, age at maturity, and longevity in Odontophrynus cf. barrioi, with skeletochronology. We also determined whether sexual dimorphism in body size exists in this species, and evaluated its relation to demographic life history traits. We found that females were larger in four variables corresponding to the morphology of the head. In addition, females of O. cf. barrioi have a longer tibia-fibula and femur than males. Nevertheless, Odontophrynus cf. barrioi shows no sexual dimorphism in snout-vent length. We suggest the possibility that sexes have different growth trajectories after the onset of reproduction, as they are exposed to different selection pressures, or even predation rate, because of size differences.